Antecedents of Organizational Performance Moderated by Gender in Indonesian Woodcarving SMEs - Bahtiar Usman; Sarfilianty Anggiani; Rycha Kuwara Sari (Rescollacom (Research Collaborations Community), 2026)
This study aims to analyze the effect of entrepreneurial strategy, strategic human resource management, and government support on organizational performance, both directly and indirectly through strategic change management as a mediating variable, as well as to examine the role of gender as a moderating variable. This study employs a quantitative method using a non-probability sampling approach, where the unit of analysis is the owner/leader of micro enterprises. A total of 120 respondents were included in the analysis. The collected data were analyzed using SmartPLS version 3. The findings reveal that entrepreneurial strategy and strategic change management have a positive effect on organizational performance, while strategic human resource management and government support do not have a direct effect on organizational performance. Furthermore, strategic human resource management and government support are found to have a positive effect on strategic change management, whereas entrepreneurial strategy does not significantly influence this variable. In indirect testing, strategic change management is proven to mediate the effect of strategic human resource management and government support on organizational performance, but it does not mediate the effect of entrepreneurial strategy. In addition, gender is found to act as a moderating variable that strengthens or weakens the relationship between strategic change management and organizational performance. These findings highlight the crucial role of strategic change management as a key mediator in improving organizational performance and demonstrate that gender functions as a boundary condition influencing the strength of relationships among variables in the model. The limitation of this study is that the respondents were limited to owners/leaders of wood carving micro-enterprises in Central Java, with limited variables and research methods. Future research is recommended to include more MSMEs with broader geographical coverage, develop research models with additional exogenous variables, and employ qualitative or mixed-method approaches.